Combined porous-monolithic TiNi materials surface-modified with electron beam for new-generation rib endoprostheses - Shabalina, Anastasiia V.; Anikeev, Sergey G.; Kulinich, Sergei A.; Artyukhova, Nadezhda V.; Vlasov, Vitaly A.; Kaftaranova, Maria I.; Khodorenko, Valentina N.; Yakovlev, Evgeny V.; Pesterev, Evgeny A.; Lukyanenko, Anna V.; Volochaev, Mikhail N.; Pakholkina, Sofiya; et al. (Journal of functional biomaterials)
TiNi alloys are very widely used materials in implant fabrication. When applied in rib replacement, they are required to be manufactured as combined porous-monolithic structures, ideally with a thin, porous part well-adhered to its monolithic substrate. Additionally, good biocompatibility, high corrosion resistance and mechanical durability are also highly demanded. So far, all these parameters have not been achieved in one material, which is why an active search in the field is still underway. In the present study, we prepared new porous-monolithic TiNi materials by sintering a TiNi powder (0–100 m) on monolithic TiNi plates, followed by surface modification with a highcurrent pulsed electron beam. The obtained materials were evaluated by a set of surface and phase analysis methods, after which their corrosion resistance and biocompatibility (hemolysis, cytotoxicity, and cell viability) were evaluated. Finally, cell growth tests were conducted. In comparison with flat TiNi monoliths, the newly developed materials were found to have better corrosion resistance, also demonstrating good biocompatibility and potential for cell growth on their surface. Thus, the newly developed porous-on-monolith TiNi materials with different surface porosity and morphology showed promise as potential new-generation implants for use in rib endoprostheses.